Triiodothyronine Induces Proliferation of Pancreatic β-cells through the MAPK/ERK Pathway - Kim, T. K.; Lee, J. S.; Jung, H. S.; Ha, T. K.; Kim, S. M.; Han, N.; Lee, E. J.; Kim, T. N.; Kwon, M. J.; Lee, S. H.; Kim, M. K.; Rhee, B. D.; Park, J. H. (Experimental and Clinical Endocrinology & Diabetes, 2014)
3,5,3’-Triiodothyronine (T3) has a stimulatory effect on cellular growth via thyroid hormone receptors (TRs) in several cell lines. TR expression in the pancreas suggests that pancreatic beta cell proliferation might be induced by T3. The purpose of this study was to demonstrate that T3 induces pancreatic beta cell proliferation through the mitogen activated protein kinase/extracellular regulated kinase (MAPK/ERK) pathway.INS-1 cells were plated as a monolayer at densities of 4×104, cultured in RPMI 1 640 with 10% fetal bovine serum with 2-mercaptoethanol, respectively, in 6-well multiplates. After 48 h, they were exposed to 10−7 M T3 or to vehicle alone. Viable cells were harvested after 24, 48, and 72 h of continuous exposure. Cell proliferation and TRα1 and TRβ1 expression were analyzed by flow-assisted cell sorting analysis, Ki-67 staining, and Western blotting. The p38 MAPK, ERK, and Akt pathways were analyzed by Western blotting. Beta cell function was evaluated by assaying insulin secretion.T3 enhanced INS-1 cell proliferation at a dose of 10−7 M in a time-dependent manner via the MAPK/ERK pathway and promoted insulin secretion.Our results demonstrate that MAPK/ERK pathway plays an important role in the T3 induced pancreatic beta cell proliferation.
Keywords: 3,5,3’-triiodothyronine (T3); thyroid hormone receptors; INS-1 cell; MAPK/ERK pathway; Akt pathway